2015
DOI: 10.1007/s10802-015-0035-6
|View full text |Cite
|
Sign up to set email alerts
|

Peer Victimization and Adolescent Adjustment: The Moderating Role of Sleep

Abstract: The present study examined multiple indices of sleep as moderators of the association between peer victimization and adjustment among typically developing adolescents. Participants included 252 adolescents (M = 15.79 years; 66% European American, 34% African American) and their parents. A multi-method, multi-informant design was employed to address the research questions. Sleep was assessed objectively with actigraphy (sleep minutes and sleep efficiency) and subjectively with self-reports. Adolescents reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 63 publications
(95 reference statements)
3
26
0
Order By: Relevance
“…The majority of past studies on the role of sleep on stress sensitivity among youth have focused on psychosocial outcomes (El-Sheikh et al, 2014; El-Sheikh et al, 2016; Lemola et al, 2012; Tu et al, 2015). Studies focusing on the HPA-axis have primarily relied on experimental inducement of acute stress and sleep loss (Goodin et al, 2012; Raikkonen et al, 2010), which may not reflect naturalistic experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of past studies on the role of sleep on stress sensitivity among youth have focused on psychosocial outcomes (El-Sheikh et al, 2014; El-Sheikh et al, 2016; Lemola et al, 2012; Tu et al, 2015). Studies focusing on the HPA-axis have primarily relied on experimental inducement of acute stress and sleep loss (Goodin et al, 2012; Raikkonen et al, 2010), which may not reflect naturalistic experiences.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, peer victimization was more strongly related to internalizing symptoms among adolescents with more perceived sleep problems compared to those with fewer perceived sleep problems (Tu et al, 2015). Similarly, perceived discrimination was related to more depressive symptoms and externalizing behaviors among adolescents with shorter sleep duration and poorer perceived sleep quality (El-Sheikh et al, 2016; Yip, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from other studies have revealed a dual‐protection or protective–reactive pattern of effects (Luthar et al ., ), in which a protective attribute (better sleep) is beneficial in low‐ but not high‐risk contexts. Supportive of this pattern, children and adolescents with the highest level of adaptation were those with longer and better quality sleep in conjunction with low familial (Bernier et al ., ; Bordeleau et al ., ; El‐Sheikh et al ., ), peer (Tu et al ., ) or sociocultural risks (Yip, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have yielded a moderation pattern of effects that is consistent with cumulative or dual risk perspectives (Evans, 2003;Sameroff, 1983), which propose that individuals may have a vulnerability that increases risk, or a protective factor that reduces risk, in the context of an environmental stressor. For instance, short or poor-quality sleep increased vulnerability for adjustment problems, whereas better sleep quality functioned as a protective factor in the context of family and peer stress (Lemola et al, 2012;Tu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Further, this study is focused on children from low‐income families, who are at relatively high risk for both self‐regulation and sleep difficulties. As suggested by prior work (Chiang et al., ; Schumacher et al., ; Tu, Erath, & El‐Sheikh, ) which is informed by the differential susceptibility model (Ellis et al., ), we hypothesize that toddler sleep will moderate the association between parenting and toddler self‐regulation such that toddlers who obtain less nighttime sleep and are exposed to negative parenting will have poorer self‐regulation skills than will those who obtain more sleep. We also examined effects of positive parenting and demographic covariates in an exploratory manner.…”
Section: Introductionmentioning
confidence: 91%